Bekasam Kuliner Kearifan Lokal Untuk Meningkatkan Keterampilan Bioteknologi Siswa Kelas IX.1 SMPN 1 Tanjung Batu - Ahmad Ardius Kidan (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The slogan "I love made in Indonesia" seems to be a mere word, because it is proven that children are more proud of foreign culture, the swiftness of globalization will in fact shift the values of indigenous traditions and culture of Indonesia, both in cities and villages. Pempek or empek-empek city is another nickname for the city of Palembang. Culinary typical of local wisdom in Palembang is not just Pempek. Bekasam is a culinary specialty of local wisdom that makes biotenology. Based on preliminary observations, abundance of fish catches, still high interest in exam, low community who have skills in making scars, recommendations from the local government to integrate local wisdom, the existence of KD and topics of biotechnology along with skills assessment in the 2013 curriculum, the authors conducted classroom action research, through two cycles with the aim of improving the skills and quality of second-hand products, data obtained from observation of performance skills and product instruments with predetermined indicators, analyzed qualitatively. The end result is an average% of process skill assessment of 92.77%, the average% of product appraisal at the end of 89.81% shows that the former as a culinary knowledge of local wisdom can improve performance skills and biotechnology products for students of class IX.1 SMP Negeri 1 Tanjung Batu. Keywords: Bekasam; Culinary; Local wisdom; Skills; Biotechnology